2016
DOI: 10.1111/jtsb.12116
|View full text |Cite
|
Sign up to set email alerts
|

Moral Motivation as a Dynamic Developmental Process: Toward an Integrative Synthesis

Abstract: The real‐life complexity of moral motivation can be examined and explained by reintegrating time and development into moral inquiry. This article is one of the possible integrative steps in this direction. A dynamic developmental conception of moral motivation can be a useful bridge toward such integration. A comprehensive view of moral motivation is presented. Moral motivation is reconceptualized as a developmental process of self‐organization and self‐regulation out of which moral judgment and action emerge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
(154 reference statements)
0
7
0
1
Order By: Relevance
“…Damon and Hart (1992) viewed moral identity as the best predictor of moral commitment and moral action, an argument that is supported by empirical research. For example, some studies have suggested that moral identity can positively predict the involvement of teenagers in community activities (Pratt et al 2003), as well as the prosocial behaviors of young adults (Kaplan 2017). The above findings indicate that there are close associations between moral awareness, moral identity, and moral conduct.…”
mentioning
confidence: 77%
“…Damon and Hart (1992) viewed moral identity as the best predictor of moral commitment and moral action, an argument that is supported by empirical research. For example, some studies have suggested that moral identity can positively predict the involvement of teenagers in community activities (Pratt et al 2003), as well as the prosocial behaviors of young adults (Kaplan 2017). The above findings indicate that there are close associations between moral awareness, moral identity, and moral conduct.…”
mentioning
confidence: 77%
“…Conscious effort. This outlook distinguishes the volitional side of self-regulated processes from other automatic or more reactive forms of regulation, as intentional and conscious effort are displayed in order to resolve control demands that arise from the internal and external environments (Gestsdóttir & Lerner, 2007;Kaplan, 2017).…”
Section: Defining Self-regulation From a Developmental Perspectivementioning
confidence: 99%
“…We are constantly busy with the question about who the I is that I am. A moral identity emerges from the long‐term self‐organization that informs concrete moral judgments (Kaplan, ). Life unfolds itself as a story of which the ‘I' is the protagonist.…”
Section: Senses Of the Individual Selfmentioning
confidence: 99%